2022
DOI: 10.3390/foods11213330
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Immunological Activity of Exopolysaccharide from Lacticaseibacillus paracasei GL1 Isolated from Tibetan Kefir Grains

Abstract: Two exopolysaccharide fractions (GL1-E1 and GL1-E2) of Lacticaseibacillus paracasei GL1 were isolated with the molecular weights of 3.9 × 105 Da and 8.2 × 105 Da, respectively. Both fractions possessed mannose, glucose, and galactose in molar ratios of 1.16:1.00:0.1, and 3.81:1.00:0.12, respectively. A structural arrangement of two fractions was proposed by methylation, one-dimensional and two-dimensional nuclear magnetic resonance experiments. The backbone of GL1-E1 consisted of →4)-α-D-Glcp(1→, →3,4)-α-D-Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…To deepen the knowledge about the characteristics of EPS produced by L. paracasei CIDCA strains and understand the relationship between EPS features and their functional properties, the degree of polymerization and the monomer composition of each EPS were studied. EPS produced by LAB present a wide range of molecular weight that varies between 10 4 and 10 6 Da for heteropolysaccharides (HePS) and up to 10 8 for homopolysaccharides (HoPS) (Ryan et al, 2015;Daba et al, 2021;Werning et al, 2022), as it was evidenced for L. paracasei strains reported in the literature (Liu et al, 2013;Wang et al, 2022). When studying the molecular weight of EPS from L. paracasei CIDCA strains, it was observed that these EPS have fractions with different molecular weight that goes from low MW fractions of 1 × 10 4 Da to high MW fractions of 5.10 6 Da.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…To deepen the knowledge about the characteristics of EPS produced by L. paracasei CIDCA strains and understand the relationship between EPS features and their functional properties, the degree of polymerization and the monomer composition of each EPS were studied. EPS produced by LAB present a wide range of molecular weight that varies between 10 4 and 10 6 Da for heteropolysaccharides (HePS) and up to 10 8 for homopolysaccharides (HoPS) (Ryan et al, 2015;Daba et al, 2021;Werning et al, 2022), as it was evidenced for L. paracasei strains reported in the literature (Liu et al, 2013;Wang et al, 2022). When studying the molecular weight of EPS from L. paracasei CIDCA strains, it was observed that these EPS have fractions with different molecular weight that goes from low MW fractions of 1 × 10 4 Da to high MW fractions of 5.10 6 Da.…”
Section: Discussionmentioning
confidence: 88%
“…With regard to EPS-producing L. paracasei strains, most of the studies report the monosaccharide composition of EPS synthetized in MRS or chemically defined medium added with different sugars. In general, EPS from L. paracasei strains are heteropolysaccharides mainly composed by glucose, mannose and galactose, along with some minor sugars such as fucose, xylose, rhamnose, arabinose, N-acetylgalactosamine, galacturonic and glucuronic acid, depending on the strain (Hee et al, 2011;Liu et al, 2013;Balzaretti et al, 2017;Bhat and Bajaj, 2019;Xiao et al, 2021;Zhang et al, 2021;Amini et al, 2022;Wang et al, 2022). In agreement with our results, EPS produced by L. paracasei DG (Balzaretti et al, 2017), L. paracasei KB28 (Hee et al, 2011) and L. paracasei KL1 (Liu et al, 2013) have also shown the presence of rhamnose in their composition.…”
Section: Discussionmentioning
confidence: 99%
“…The backbone of GL1-E2 consisted of →4)-α- d -Glc p (1→, →3,4)-α- d -Man p (1→, →3,6)-α- d -Man p (1→, →6)-α- d -Man p (1→, →6)-α- d -Gal p (1→ and →4)-β- d -Man p (1→, and the side chain also consisted of α- d -Man p residue. 14 The existence of β-(2→1) linkages was more vulnerable to the reaction of enzymes. The different structures including the M w , glycosidic bond, and connection types of GL1-E1 and GL1-E2 were the reasons for the different growth curves of the strains.…”
Section: Resultsmentioning
confidence: 99%
“…Its physicochemical structure, thermal stability, and biological activity were investigated. 14 However, little information is available on the digestive characteristics of EPS from L. paracasei isolated from kefir. Therefore, to understand the detailed changes in the chemical structures of GL1-E1 and GL1-E2 during the digestion and fermentation processes of human intestinal microflora, GL1-EPS was used as a carbon source for the growth of ten potential probiotic strains.…”
Section: Introductionmentioning
confidence: 99%
“…Four cytokine levels including NO, IL-6, TNF-α and IL-1β cytokines were measured according to [28]. Initially, macrophages were treated with PBSR1 (25-200 µg/mL) or LPS (10 µg/mL) for 24 h. Then, the supernatants were collected for the level determination of NO, IL-6, TNF-α and IL-1β following a commercial ELISA kit's instructions.…”
Section: Cytokines Productionmentioning
confidence: 99%